Effects of the urban heat island and climate change on the growth of Khaya senegalensis in Hanoi, Vietnam - Astrid Moser-Reischl; Enno Uhl; Thomas Rötzer; Peter Biber; Tran van Con; Nguyen Thanh Tan; Hans Pretzsch (Forest Ecosystems, 2018)
Abstract Background Recent projections expect that Vietnam will be affected most severely by climate change with higher temperatures, more precipitation and rising sea levels. Especially increased temperatures will worsen the situations in cities, amplifying the urban heat island effect. Green infrastructures, i.e. urban trees are a common tool to improve the urban micro-climate for humans. Vital and well growing trees provide greatest benefits such as evaporative cooling, shading, air filtering and carbon storage. However, urban tree growth is often negatively affected by urban growing conditions such as high soil sealing with compacted tree pits providing small growing spaces with limited water, nutrient and oxygen supply, further warm temperatures and high pollution emissions. This study analyzed the growth of urban and rural African mahogany (Khaya senegalensis (Desr.) A. Juss.) trees in the city of Hanoi, Vietnam and the effects of the surrounding climate conditions on tree growth. Results The results showed that rural African mahogany trees grew better than trees situated in the city center, which is contrary to other results on tree growth of temperate and subtropical cities worldwide. Moreover tree growth was similar regardless of the time of growth. Other results regarding stem growth of African mahogany located in different areas of Hanoi (east, west, north, city center) revealed a better growth in the northern and western outskirts of the city compared to the growth of trees in the city center. Conclusion African mahogany trees in the urban centers of Hanoi showed a decreased growth compared to rural trees, which was likely induced by a low ground-water level and high pollution rates. In view of climate change and global warming, the decreased tree growth in the city center may also affect tree service provision such as shading and cooling. Those climate mitigation solutions are strongly needed in areas severely affected by climate change and global warming such as Vietnam.